By and for the people - Scheinerman, Naomi (The Hastings Center report, 2014)
In the eighteenth century, David Hume posited, “And though the philosopher may live remote from business[,] . . . philosophy, if carefully cultivated by several, must gradually diffuse itself throughout the whole society, and bestow a similar correctness on every art and calling.” While asking a lot, Hume nonetheless articulates some of the hopes I brought to The Hastings Center two years ago. In my work here, I often consider how to best allocate time to ask both, what is the moral message? and, how can we use that moral message to better the world?